STRUCTURAL STUDIES ON SILK PROTEIN FIBRE FROM PSEUDOSCORPION : Life Science-Bio technology - ANNAMALAI, MEENAKSHI; K.JAYAPRAKASH (International Journal of Life Science and Pharma Research, 2012)
Pseudoscorpion species were collected from Western Ghat’s forest habitat. They were identified as Chelifer sp. of order cheliferoidea to the class Arachnida (Mahnert, 1991). The silk gland of chelicerae was dissected out. The samples of the fibroin protein secreted from the silk gland were subjected for physical, chemical and biological analysis. It was found that false scorpion fiber could be dissolved in 6N HCL / 50% propionic acid medium. The amino acid composition was recalled the blend of amino acids present in the fibrous protein of spider and Bombyx mori. The structural studies suggesting collogenous in nature and a releationship with silk fibers of spider and silk insect. The results are discussed with earliar literature.